Why does this matrix give the derivative of a function?

I happened to stumble upon the following matrix: $$ A = \begin{bmatrix} a & 1 \\ 0 & a \end{bmatrix} $$

And after trying a bunch of different examples, I noticed the following remarkable pattern. If $P$ is a polynomial, then: $$ P(A)=\begin{bmatrix} P(a) & P'(a) \\ 0 & P(a) \end{bmatrix}$$

Where $P'(a)$ is the derivative evaluated at $a$.

Futhermore, I tried extending this to other matrix functions, for example the matrix exponential, and wolfram alpha tells me: $$ \exp(A)=\begin{bmatrix} e^a & e^a \\ 0 & e^a \end{bmatrix}$$ and this does in fact follow the pattern since the derivative of $e^x$ is itself!

Furthermore, I decided to look at the function $P(x)=\frac{1}{x}$. If we interpret the reciprocal of a matrix to be its inverse, then we get: $$ P(A)=\begin{bmatrix} \frac{1}{a} & -\frac{1}{a^2} \\ 0 & \frac{1}{a} \end{bmatrix}$$ And since $f'(a)=-\frac{1}{a^2}$, the pattern still holds!

After trying a couple more examples, it seems that this pattern holds whenever $P$ is any rational function.

I have two questions:

  1. Why is this happening?

  2. Are there any other known matrix functions (which can also be applied to real numbers) for which this property holds?


Solution 1:

If $$ A = \begin{bmatrix} a & 1 \\ 0 & a \end{bmatrix} $$ then by induction you can prove that $$ A^n = \begin{bmatrix} a^n & n a^{n-1} \\ 0 & a^n \end{bmatrix} \tag 1 $$ for $n \ge 1 $. If $f$ can be developed into a power series $$ f(z) = \sum_{n=0}^\infty c_n z^n $$ then $$ f'(z) = \sum_{n=1}^\infty n c_n z^{n-1} $$ and it follows that $$ f(A) = \sum_{n=0}^\infty c_n A^n = I + \sum_{n=1}^\infty c_n \begin{bmatrix} a^n & n a^{n-1} \\ 0 & a^n \end{bmatrix} = \begin{bmatrix} f(a) & f'(a) \\ 0 & f(a) \end{bmatrix} \tag 2 $$ From $(1)$ and $$ A^{-1} = \begin{bmatrix} a^{-1} & -a^{-2} \\ 0 & a^{-1} \end{bmatrix} $$ one gets $$ A^{-n} = \begin{bmatrix} a^{-1} & -a^{-2} \\ 0 & a^{-1} \end{bmatrix}^n = (-a^{-2})^{n} \begin{bmatrix} -a & 1 \\ 0 & -a \end{bmatrix}^n \\ = (-1)^n a^{-2n} \begin{bmatrix} (-a)^n & n (-a)^{n-1} \\ 0 & (-a)^n \end{bmatrix} = \begin{bmatrix} a^{-n} & -n a^{-n-1} \\ 0 & a^{-n} \end{bmatrix} $$ which means that $(1)$ holds for negative exponents as well. As a consequence, $(2)$ can be generalized to functions admitting a Laurent series representation: $$ f(z) = \sum_{n=-\infty}^\infty c_n z^n $$

Solution 2:

It's a general statement if $J_{k}$ is a Jordan block and $f$ a function matrix then \begin{equation} f(J)=\left(\begin{array}{ccccc} f(\lambda_{0}) & \frac{f'(\lambda_{0})}{1!} & \frac{f''(\lambda_{0})}{2!} & \ldots & \frac{f^{(n-1)}(\lambda_{0})}{(n-1)!}\\ 0 & f(\lambda_{0}) & \frac{f'(\lambda_{0})}{1!} & & \vdots\\ 0 & 0 & f(\lambda_{0}) & \ddots & \frac{f''(\lambda_{0})}{2!}\\ \vdots & \vdots & \vdots & \ddots & \frac{f'(\lambda_{0})}{1!}\\ 0 & 0 & 0 & \ldots & f(\lambda_{0}) \end{array}\right) \end{equation} where \begin{equation} J=\left(\begin{array}{ccccc} \lambda_{0} & 1 & 0 & 0\\ 0 & \lambda_{0} & 1& 0\\ 0 & 0 & \ddots & 1\\ 0 & 0 & 0 & \lambda_{0} \end{array}\right) \end{equation} This statement can be demonstrated in various ways (none of them short), but it's a quite known formula. I think you can find it in various book, maybe in Horn, Johnson, Matrix Analisys.